EDUKASI IBU HAMIL TENTANG STUNTING DI RS PURI BUNDA TABANAN - Putu Adi Cahya Dewi; Kadek Primadewi; Desak Made Firsia sastra Putri (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2022)
The first 1000 days are a golden period in a child's development. Several studies have stated that stunting can be prevented by paying attention to the first 1000 days of life, including during pregnancy. This service is carried out to increase mother's knowledge regarding stunting prevention since pregnancy at Puri Bunda Tabanan General Hospital on October 23, 2022 as a form of collaboration with STIKES Advaita Medika Tabanan in accelerating the reduction of stunting in Tabanan in particular and Indonesia in general. After education about stunting was conducted, mothers who attended the educational activities were committed to improving nutritional intake and maintaining physical and mental health of mothers during pregnancy so that later they could give birth to a physically and mentally healthy generation and avoid the risk of stunting or failure to thrive